Culture of Fresh Water Prawn Macrobrachium rosenbergii and Its Cost Benefit Analysis Using Low Cost Feed - Anbalagan R.; Nazar , A. R.; Sivakami R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Fresh water prawn culture has great potential for rural aquaculture, generating considerable employment and income for rural and poor people. Fresh water prawn farming is environmentally sustainable as it is usually practiced in low stocking density. Fresh water prawn culture has attracted more attention in the recent years due to its export potential and increasing demand as good protein. The seeds of Macrobrachium rosenbergii were collected from Thanjavur breeders and immunized seedling were introduced into the culture ponds. The stocking density 1200 numbers/pond. The size of fingerlings from 4 to 8 cm. The feed were given to the prawn which was consisted of fish meal 20%, soya meal 9%, rice brown 45%, coconut oil cake 20%, tapioca starch 5% and mineral premix 1%. Total body weight of 10% feed every day. The water quality of the culture pond during the period of culture within the range of water quality parameters. In culture pond with an average stocking size of 3-5 g (average 4 g), the growth at the end of six months ranged between 30.5 g and 56.5 g, the average weight being 48.5 g. The total weight of the prawns at the time of harvest was 50.325 kg. The prawns were sold in two lots. The ones with the bigger size 38.5 kg were sold at Rs.650/kg, while the while the smaller prawns weighing 11.8 kg were sold at Rs. 500/kg. The bigger prawns yielded Rs. 25025, while the smaller ones yielded Rs.5900. Thus, the total income from prawn culture yielded Rs.30925. The total expenditure incurred for this culture amounted to Rs.12800. Thus the total profit from this culture worked out to Rs.18125. When this profit is calculated on a monthly basis, it works out to Rs.3020.8 This study proves that culturing M. rosenbergii is profitable even in small ponds which can economically benefit the lives of the local people.